Agro-ecology in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
seventh scientific conference of IFOAM (International Federation of Organic Agricultural Movements) Ouagadougou from January 2 to 5, 1989